SOCIAL ACCOUNTING. - Powelson, John P. (The Accounting Review, 1955)
Just as accounting is an indispensable tool for business executives and researchers in finance and management, so also is it becoming more and more important to economists in both industry and government. Over the past thirty years a new branch of accounting has been developed, in which the transactions of a nation rather than a business enterprise are pictured. Data from these accounts are valuable in assessing the overall business picture, the prospects for full employment and prosperity, the strength of foreign markets, the approach of currency convertibility, and a host of other facts vital to businessmen and economists alike. National income accounts appear in courses in income and employment or business cycles, while balance of payments accounting is dealt with in the study of international trade. The present article is intended to point out areas in which accounting departments can be of service to liberal arts students, particularly economics majors, who are learning the social accounts.